2015
DOI: 10.1016/j.drugalcdep.2015.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent substance use and educational attainment: An integrative data analysis comparing cannabis and alcohol from three Australasian cohorts

Abstract: Background:The relative contributions of cannabis and alcohol use to educational outcomes are unclear. We examined the extent to which adolescent cannabis or alcohol use predicts educational attainment in emerging adulthood.Methods: Participant-level data were integrated from three longitudinal studies from Australia and New Zealand (Australian Temperament Project, Christchurch Health and Development Study, and Victorian Adolescent Health Cohort Study). The number of participants varied by analysis (N=2179-367… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 32 publications
9
64
1
6
Order By: Relevance
“…8 Cannabis is used widely by young people throughout the world. 18,19 In a study, it was concluded that young people aged between 12-17 years purchased cannabis more than those aged between 50 and 64 years, and the use of cannabis was greater in amongst the young. In the same study, the use of cannabis was reported stated to be higher amongst males compared with females.…”
Section: Discussionmentioning
confidence: 99%
“…8 Cannabis is used widely by young people throughout the world. 18,19 In a study, it was concluded that young people aged between 12-17 years purchased cannabis more than those aged between 50 and 64 years, and the use of cannabis was greater in amongst the young. In the same study, the use of cannabis was reported stated to be higher amongst males compared with females.…”
Section: Discussionmentioning
confidence: 99%
“…Dans notre étude, les élèves qui ont commencé à s'adonner aux abus occasionnels d'alcool ont présenté, comme prévu, un risque accru de manque d'efforts et de faible rendement, qui était plus marqué lorsque les abus occasionnels d'alcool ont commencé avec une fréquence plus élevée, mais sur le plan de leurs attentes et aspirations à l'égard des études, les résul-tats des modèles étaient nuls ou allaient dans le sens opposé. Les associations relevées dans la documentation scientifique entre l'alcool et l'édu-cation sont moins robustes et moins constantes qu'avec autres substances pouvant donner lieu à une consommation abusive 21,22,27 . Certains experts ont avancé la théorie que la consommation d'alcool est davantage compatible avec la réussite scolaire que la consommation de drogues 22 .…”
Section: Analyses Statistiquesunclassified
“…Par exemple, la consommation excessive d'alcool chez les jeunes a été associée à des notes plus faibles [3][4][5][6][7][8][9][10][11][12][13][14][15][16] , à l'absentéisme 13,[17][18][19] et à l'abandon des cours 20 . Toutefois, la littérature scientifique présente de nombreux résultats contradictoires 21,22 . En outre, les causes des associations présumées entre la consommation de substances et la réussite scolaire sont encore mal connues.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In longer-term studies, they are less likely to graduate high school and attain a college degree [63,64]. Other studies have shown that adolescent marijuana users are more likely to be addicted to other drugs after adolescence, including tobacco, alcohol, and opioid analgesics [65][66][67][68][69][70].…”
Section: Adolescent Usementioning
confidence: 99%